Influence of Severe Plastic Deformation by Extrusion on Microstructure, Deformation and Thermal Behavior under Tension of Magnesium Alloy Mg-2.9Y-1.3Nd; Metals; Vol. 13, iss. 5 - Legostaeva E. V. Elena Viktorovna; Eroshenko A. Yu. Anna Yurjevna; Vavilov V. P. Vladimir Platonovich; Skripnyak V. A. Vladimir Albertovich; Luginin N. A. Nikita Andreevich; Chulkov A. O. Arseniy Olegovich; Kozulin A. A. Aleksandr Anatoljevich; Skripnyak V. V. Vladimir Vladimirovich; Schmidt J. Jurgen; Tolmachev A. I. Aleksey Ivanovich; Uvarkin P. V. Pavel Viktorovich; Sharkeev Yu. P. Yury Petrovich (2023, 2023)
Title screen